Role of sfk1 Gene in the Filamentous Fungus Penicillium roqueforti - Torrent, Claudia; Gil-Durán, Carlos; Rojas-Aedo, Juan F.; Medina, Exequiel; Vaca, Inmaculada; Castro, Paulo; García-Rico, Ramón O.; Cotoras, Milena; Mendoza, Leonora; Levicán, Gloria; Chávez, Renato (Frontiers in Microbiology, 2017)
The sfk1 (suppressor of four kinase) gene has been mainly studied in Saccharomyces cerevisiae, where it was shown to be involved in growth and thermal stress resistance. This gene is widely conserved within the phylum Ascomycota. Despite this, to date sfk1 has not been studied in any filamentous fungus. Previously, we found that the orthologous of sfk1 was differentially expressed in a strain of Penicillium roqueforti with an altered phenotype. In this work, we have performed a functional characterization of this gene by using RNAi-silencing technology. The silencing of sfk1 in P. roqueforti resulted in decreased apical growth and the promotion of conidial germination, but interesting, it had no effect on conidiation. In addition, the attenuation of the sfk1 expression sensitized the fungus to osmotic stress, but not to thermal stress. RNA-mediated gene-silencing of sfk1 also affected cell wall integrity in the fungus. Finally, the silencing of sfk1 depleted the production of the main secondary metabolites of P. roqueforti, namely roquefortine C, andrastin A and mycophenolic acid. To the best of our knowledge this is the first study of the sfk1 gene in filamentous fungi.